Horizontal Learning and Management: Internal Potential for Developing School into Learning Community - Јelena D. Đermanov; Isidora D. Korać (Inovacije u Nastavi, 2023)
In this paper, teachers’ horizontal learning is discussed from the perspective of creating a stimulating environment for its implementation. The questions of the role and competence of the school principal in that process have been analyzed, as well as the questions of whether and how the school can develop into a learning community by means of teachers’ joint collaborative learning. In the main part of the paper, we point out the importance of the systemic approach in understanding the interdependence of individual and organizational learning processes within the school, as well as the key influence of the principal in modeling these processes in the transformation of the school into a learning community. The conclusion is that the complexity of organizational processes aimed at improving quality, which in the school context are much easier to prevent than to start and manage them, implies the appropriate competencies of the principal as a leader and/or manager.